Adoptees facing adolescence: What accounts for their psychological well-being?. (June 2021) - Ranieri, Sonia; Ferrari, Laura; Danioni, Francesca Vittoria; Canzi, Elena; Barni, Petra; Rosnati, Rosa; Rodriguez, Maite Roman
Abstract: Introduction: In accordance with the "resilience paradigm", this study was aimed at exploring the role of the parent-child relationship in supporting internationally adopted adolescents' ability to develop a strong adoptive identity and a feeling of satisfaction with their own life. Methods: Participants were 105 Italian adopted adolescents (13–17 years) asked to complete a self-report questionnaire. Results: Results showed that adolescents generally feel fairly comfortable discussing adoption-related issues (especially with their mothers), have a medium-high level of adoptive identity, and appear to be quite satisfied with their life. Moreover, while adoptive identity mediates the association between openness in communication regarding adoption and adoptees' well-being with mothers, father-child communication openness has a direct influence on well-being. Conclusions: Findings highlighted that the quality of mother-child and father-child relationship plays a crucial role in guiding the process of adoptees' identity formation and influencing their well-being. Recommendations for professionals working with adoptive families were discussed.